Circle b:

Diameter = x

Radius =

Area =

Circle a:

Diameter =

Radius =

Area =

Thus,

Area of circle b to area of circle a

=

÷

=

×

= 4

Hence, the area of circle b is

**4 times** the area of circle a.

Quadratic formula

for the equation

ax^2+bx+c=0

x=

we are given

x^2-4x+3=0

we don't need to use quadratc formula, we just factor into

(x-3)(x-1)=0

x=3 and 1

but if you want to use quadratic, ok

x^2-4x+3=0

a=1

b=-4

c=3

input

x=

x=

x=

x=

x=2+/-1

x=2+1 or 2-1

x=3 or 1

**Answer:**

**Step-by-step explanation:**

In order to answer this question you will have to subtract 3 1/3 from 12 1/4 by turning the mixed fractions into improper fractions, finding the common denominator, (CD) then subtracting the numerators.

Turn the mixed fractions into improper fractions:

Find the common denominator:

Now subtract the numerators:

Turn the improper fraction into a mixed fraction:

Hope this helps.

You can break down linear combination method in following steps:

1) Arrange the like terms in columns (x bellow x, y bellow y...)

2) Multiply one or both equations until you "kill" one of the terms

This means that coefficients on one of your terms have the same value but have opposite signs.

3) Add equations and repeat steps 1 and 2 if you had more than two equations to start with.

So to start with we write equations with like terms in columns.

<span>4j−2k=26

5j−2k=35

All we have to do now is multiply the second equation by (-1).

</span>

4j -2k=26

-5j+2k=-35

<span>Now we can add them together and solve for j.

-j=-9

j=9

We can find k simply by plugging in j=9.

</span>4(9)−2k=26

36−2k=26

<span>2k=36-26

k=5

</span>

**Answer:**

-2

**Step-by-step explanation:**

Get y by itself.